The theory of capital - International Economic Association; Lutz, Friedrich A.; Hague, D. C. (London : Macmillan, 1961)
The book is divided into six parts: Part I. Some Conceptual Problems. Part II. Empirical Evidence. Part III. Micro-Economic Models. Part IV. Macro-Economic Models. Part V. The Theory of Income Distribution. Part VI. Report on the Proceedings.
Includes Index
rpm 09/11/2017
Loans
Keywords: Capital